(untitled) - Wehr, M. Russell (London, 1960)
Physics of the Atom is designed to meet the modern need for a better understanding of the atomic age. It is an introduction suitable for students with a background in university physics and mathematical competence at the level of calculus. This book is designed to be an extension of the introductory university physics course into the realm of atomic physics. It should give students a proficiency in this field comparable to their proficiency in mechanics, heat, sound, light, and electricity.
Keywords: Atoms,Physics